Philosophy and the mirror of nature - Rorty, Richard (Princeton Classics Ser., 2009)
30 years ago Richard Rorty argued that philosophers had developed an unhealthy obsession with the notion of representation: comparing the mind to a mirror that reflects reality. The book now stands as a classic of 20th-century philosophy.